KEJUJURAN DAN ETIKA DALAM KONSEP POLITIK MACHIAVELLI - Nashar Akbar Muhammad; R. Yuli Akhmad Hambali (UIN Sunan Gunung Djati Bandung, 2021)
This article examines honesty and ethics in Machiavelli's concept of politics. This study is very important considering that Machiavelli is often referred to as an antagonist in the world of politics. His works are often misunderstood and interpreted as a suggestion to seize power at all costs. Therefore, this article is intended to provide an honest and proportional picture of Machiavelli's thoughts which are often interpreted as immoral and disregard for ethics. Literature study was chosen as the method used to analyze Machiavelli's political thoughts. In a number of literatures, the political thought initiated by Machiavelli is often seen as a strategy to overthrow power in a cruel way. On the contrary, Machiavelli always gives advice to gain power and defend it in a humanist way. As for what is considered cruel, it aims to enforce the law. Executing certain individuals would protect a much larger group. Making Italy a strong and prosperous country is Machiavelli's greatest wish. Machiavelli has done various ways to make this happen, because for him, nothing is more important to power than the welfare of the people and the creation of a strong state